To transform the equation \( 4x + y = -12 \) to slope-intercept form, which is \( y = mx + b \) (where \( m \) is the slope and \( b \) is the y-intercept), follow these steps:
-
Start with the original equation: \[ 4x + y = -12 \]
-
Solve for \( y \) by isolating it on one side of the equation. Subtract \( 4x \) from both sides: \[ y = -4x - 12 \]
Now, the equation is in slope-intercept form, and we see that:
- The slope \( m = -4 \)
- The y-intercept \( b = -12 \)
So the correct transformation is: \[ y = -4x - 12 \]
Thus, the correct response from the options given is: y = −4x − 12.